Использование искусственных нейронных сетей для разработки катализаторов - Альами, Давид Абдель Мутталеб; Булавин, Виктор Иванович (НТУ "ХПИ", 2011)
Application of artificial neural networks (ANN) using in the field of catalysis is important both from theoretical and practical points of view. The purpose of this review is the estimation of ANN possibilities for industrial catalysts development and selection of optimum conditions for catalytic systems. Advantages of the ANN using for catalysts composition optimization in comparison with existing traditional methods are shown.
Keywords: катализ; катализатор; нейронная сеть; нейрон; синапсы; синаптическая связь